2007
DOI: 10.1200/jco.2007.11.3357
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Controlled Trial of Irinotecan Plus Infusional, Bolus, or Oral Fluoropyrimidines in First-Line Treatment of Metastatic Colorectal Cancer: Results From the BICC-C Study

Abstract: FOLFIRI and FOLFIRI+Bev offered superior activity to their comparators and were comparably safe. An infusional schedule of FU should be the preferred irinotecan-based regimen in first-line metastatic colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
448
5
15

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 712 publications
(497 citation statements)
references
References 18 publications
29
448
5
15
Order By: Relevance
“…[2][3][4] For the subgroup of patients with limited metastatic disease in the liver, nonrandomized studies have shown that patients who can undergo resection of liver metastases have 5-year survivals of 30% to 40%. [18][19][20] As a result, the integration of aggressive local therapy along with systemic treatment has been playing an increasingly important role in treatment for this disease.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] For the subgroup of patients with limited metastatic disease in the liver, nonrandomized studies have shown that patients who can undergo resection of liver metastases have 5-year survivals of 30% to 40%. [18][19][20] As a result, the integration of aggressive local therapy along with systemic treatment has been playing an increasingly important role in treatment for this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Scheithauer et al 182 Cochrane Database 183 Saltz et al 120 and de Gramont et al 131 Goldberg et al 135 and Fuchs et al 121 Hurwitz et al 146 Tumor invades submucosa T 2 Tumor invades muscularis propia T 3 Tumor invades through the muscularis propria into the subserosa T 4 Tumor directly invades other organs or structures, or perforates visceral Peritoneum Regional lymph nodes (N) N x…”
Section: Adapted With Permission From Meyerhardt and Mayer 31mentioning
confidence: 99%
“…The combination of capecitabine with irinotecan (XELIRI) plus Bev resulted in a disease control rate of 72-82% and median PFS of 9-12 months (Reinacher-Schick et al, 2008;Renouf et al, 2012;Pectasides et al, 2012;Ducreux et al, 2013). On the other hand, earlier trials evaluating chemotherapy regimen with capecitabine and irinotecan had showed that CAPIRI regimen was associated with unacceptable incidences of severe gastrointestinal adverse effects with grade 3-4 diarrhea up to 36% of patients (Rothenberg et al, 2001;Fuchs et al, 2007;Koopman et al, 2007). In the randomized phase II trial performed by Fuchs et al (BICC-C), three regimens were evaluated (FOLFIRI, modified IFL or CAPIRI) and the authors were obtained median PFS times 7.6 months for FOLFIRI, 5.9 months for mIFL and 5.8 months for CAPIRI, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Because of toxicity, further enrollment onto CAPIRI was discontinued. After the amendment to add Bev, the authors achieved the median OS interval for 19.2 months for mIFL-Bev, while it has not been reached for FOLFIRI-Bev (Fuchs et al, 2007). In a retrospective study of Ocvirk et al (2011) the authors reported that no DOI:http://dx.doi.org/10.7314/APJCP.2013.14.4.2283 significant differences were observed between patients treated with XELIRI or FOLFIRI in combination with Bev with respect to PFS, OS and oRR.…”
Section: Discussionmentioning
confidence: 99%